How to strengthen the contribution of the private sector to African development by improving its financing? - (:unkn) unknown (My University, 2021)
The private sector plays a crucial role in promoting the sustainable development. It is generally accepted that firms creates wealth, generates jobs and thus contributes to improving the living conditions of populations; while being able to increasingly ensure the preservation of natural resources, biodiversity and the climate and promoting the emancipation of women.
Keywords: African Research